2021
DOI: 10.3389/fonc.2021.721821
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Potential of 18F-FET PET in the Differential Diagnosis of Glioma Recurrence and Treatment-Induced Changes After Chemoradiation Therapy

Abstract: BackgroundMRI-based differential diagnosis of glioma recurrence (GR) and treatment-induced changes (TICs) remain elusive in up to 30% of treated glioma patients. We aimed to determine 18F-FET PET diagnostic performance in this clinical scenario, its outcome dependency on established prognostic factors, optimal 18F-FET semi-quantitative thresholds, and whether 18F-FET parameters may instantly predict progression-free survival (PFS) and overall survival (OS).MethodsWe retrospectively analyzed 45 glioma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…A recent retrospective study analyzed 45 glioma patients treated with chemotherapy that underwent [ 18 F]FET to discriminate between glioma recurrence and treatmentinduced changes. The results indicated that [ 18 F]FET PET imaging provided a good diagnostic performance (sensitivity: 86.2% (95% CI: 68.3-96.1%) and specificity 81.3% (95% CI: 54.4-96.1%)) [24], in line with another recent clinical study [25], while no gold standard for actual tumor progression was used. Interestingly, these studies also highlighted that [ 18 F]FET accuracy in diagnosis was reduced in patients with IDH-mutant gliomas.…”
Section: [ 18 F]fet and Other Amino Acid Pet Ligandssupporting
confidence: 74%
“…A recent retrospective study analyzed 45 glioma patients treated with chemotherapy that underwent [ 18 F]FET to discriminate between glioma recurrence and treatmentinduced changes. The results indicated that [ 18 F]FET PET imaging provided a good diagnostic performance (sensitivity: 86.2% (95% CI: 68.3-96.1%) and specificity 81.3% (95% CI: 54.4-96.1%)) [24], in line with another recent clinical study [25], while no gold standard for actual tumor progression was used. Interestingly, these studies also highlighted that [ 18 F]FET accuracy in diagnosis was reduced in patients with IDH-mutant gliomas.…”
Section: [ 18 F]fet and Other Amino Acid Pet Ligandssupporting
confidence: 74%
“…21 Other publications suggested that FET PET/CT is a useful noninvasive tool for prognosis of brain tumors. [22][23][24] There was no false-positive case in our study for PSMA PET. However, there was 1 patient with grade III oligodendroglioma whose lesion did not show significant PSMA uptake (patient 8).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a subgroup analysis suggested that the diagnostic accuracy was only 67% in patients with IDH-mutant gliomas compared to 91% in IDH-wildtype glioma patients [69]. On the other hand, in subsequent studies the latter finding could be confirmed only partially [70][71][72], indicating that further studies in this subgroup of patients with IDH-mutant gliomas are warranted.…”
Section: Differentiation Of Treatment-related Changes From Glioma Pro...mentioning
confidence: 99%